1993
DOI: 10.1152/ajpregu.1993.264.2.r290
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide: a selective cardiovascular peptide

Abstract: Studies were performed in three groups of anesthetized dogs to compare the structurally related peptides atrial natriuretic peptide (ANP) and C-type natriuretic peptide (CNP). Group 1 (n = 5) and group 2 (n = 4) received intravenous infusions of CNP or ANP respectively at doses of 10 ng.kg-1.min-1 and 100 ng.kg-1.min-1. Group 3 (n = 5) received CNP intrarenally at doses of 1 ng.kg-1.min-1 and 5 ng.kg-1.min-1. Intravenous infusion of CNP resulted in a greater decrease in blood pressure when compared with ANP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 0 publications
5
68
0
Order By: Relevance
“…In agreement with our findings, early studies of the biological activity of CNP in rats showed it to be natriuretic, diuretic, and a vasodepressor when injected intravenously, but the potency of CNP was about 1 % of the related hormones ANP and BNP (38). CNP, given to anesthetized dogs had greater hemodynamic activity than ANP, but it was not natriuretic even when administered directly into the renal artery (46,48) . The observation of no change in sodium excretion is unique to this peptide when compared with ANP or BNP, which in previous studies produced marked natriuresis despite similar systemic hemodynamic changes (49).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our findings, early studies of the biological activity of CNP in rats showed it to be natriuretic, diuretic, and a vasodepressor when injected intravenously, but the potency of CNP was about 1 % of the related hormones ANP and BNP (38). CNP, given to anesthetized dogs had greater hemodynamic activity than ANP, but it was not natriuretic even when administered directly into the renal artery (46,48) . The observation of no change in sodium excretion is unique to this peptide when compared with ANP or BNP, which in previous studies produced marked natriuresis despite similar systemic hemodynamic changes (49).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in accordance with previously published data showing that CNP does not influence renal function in humans and dogs after i.v. administration at low dosages (33,34). It has been demonstrated that systemic infusion or bolus administration of supraphysiological CNP concentrations in dogs increased aldosterone release and distal nephron sodium reabsorption, suggesting that CNP regulates tubular reabsorption and not glomerular filtration rate (35).…”
Section: Discussionmentioning
confidence: 99%
“…Of the three NPs, CNP has been shown to be most potent at inhibiting growth‐factor–induced smooth muscle cell migration 81. CNP has only minimal renal actions, but it has been shown to induce vasorelaxation and, interestingly, CNP infusion to dogs has been shown to lower blood pressure more effectively than ANP without natriuretic effect 82. Plasma levels of CNP1‐53 are also elevated in patients with acute decompensated HF,83 and recent data suggest that in addition to CNP1‐22, the CNP1‐53 peptide also has biological actions in in vitro and in vivo models 84.…”
Section: Cnp In the Diseased Heartmentioning
confidence: 99%